2009
DOI: 10.1055/s-0029-1233459
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Circulating N-terminal pro-Brain Natriuretic Peptide (NT-proBNP) and Adiponectin Concentrations Depend on Obesity Level in Female Adolescents: Gender Dimorphic Findings

Abstract: N-terminal pro-Brain Natriuretic Peptide (NT-proBNP) is an established biomarker for heart failure in adults, while its plasma concentrations are altered in adult obesity. Plasma adiponectin concentrations are decreased in obesity and low levels are associated with disorders with an increased cardiometabolic risk. A few studies support an association between these two markers in adults with coronary heart disease. Such relations have not been investigated in children with obesity, which is the most prevalent r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 20 publications
0
5
1
Order By: Relevance
“…1 Furthermore, plasma NT-proBNP concentrations did not correlate with SBP and DBP neither in girls nor in boys, although among the obese boys plasma NT-proBNP concentrations correlated significantly with SBP (r=0.45, P=0.03). 17 In a second report from the same population, 18 focusing further on metabolic relationships, plasma NT-proBNP concentrations correlated negatively with HDL-cholesterol (r=-0.36, P=0.03) in boys, a finding in contrast with our findings, whereas no significant correlations were found between plasma NT-proBNP and glucose, insulin, HOMA index, cholesterol and triglycerides. In these studies, no further adjusted analyses or interaction analyses were reported.…”
Section: Nps In Children and Adolescentscontrasting
confidence: 96%
See 1 more Smart Citation
“…1 Furthermore, plasma NT-proBNP concentrations did not correlate with SBP and DBP neither in girls nor in boys, although among the obese boys plasma NT-proBNP concentrations correlated significantly with SBP (r=0.45, P=0.03). 17 In a second report from the same population, 18 focusing further on metabolic relationships, plasma NT-proBNP concentrations correlated negatively with HDL-cholesterol (r=-0.36, P=0.03) in boys, a finding in contrast with our findings, whereas no significant correlations were found between plasma NT-proBNP and glucose, insulin, HOMA index, cholesterol and triglycerides. In these studies, no further adjusted analyses or interaction analyses were reported.…”
Section: Nps In Children and Adolescentscontrasting
confidence: 96%
“…Several smaller studies (n<150), almost all hospital-based, [17][18][19][20][21][22][23] have studied the relationships between NPs and anthropometry, metabolism and BP in children and adolescents. The studies are heterogeneous, and the results are conflicting.…”
Section: Nps In Children and Adolescentsmentioning
confidence: 99%
“…Recently, the association between NT-proBNP and adiponectin has been examined in adults with heart failure [5,30,31]. Some studies stated that the association of APN and heart failure vanished after adjusting for NT-proBNP [31], some revealed that high APN level was associated with increased risk of mortality, independent of plasma NT-proBNP [22], while Dai Z et al found an improved diagnostic value of conjunction of NT-proBNP and APN for heart failure [30].…”
Section: Adiponectin and Nt-probnpmentioning
confidence: 99%
“…Though plenty of biomarkers assessing the reversibility or disease severity have been reported in previous work, only N-terminal pro-Brain Natriuretic Peptide (NT-proBNP) correlates well with hemodynamic parameters and survival in PH patients and thus has been incorporated in clinical PH guidelines [ 4 ]. Recent studies suggest a positive association between adiponectin (APN) and NT-proBNP in heart failure patients [ 5 , 6 ]. Furthermore, adiponectin has been found to be elevated in patients with pulmonary hypertension [ 7 , 8 ] and positively correlated with increased blood flow and vascular resistance [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent investigations reported gender differences in the relationship between adiponectin levels and obesity with strong association between low adiponectin plasma levels and obesity among women (EGLIT et al, 2013;PERVANIDOU et al, 2009;URBINA et al, 2009). Therefore, the current study will examine the relationship of obesity measures with adiponectin in different polymorphism genotypes among young adult women.…”
Section: Introductionmentioning
confidence: 97%